2022
DOI: 10.1002/jbt.23079
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the potential mechanisms underlying carbendazim‐induced hepatorenal toxicity in rats

Abstract: Carbendazim (CBZ) is a common environmental pollutant that can contaminate food and water and severely damage human health. Some studies revealed the adverse effect of CBZ on different organs, but its detailed toxicity mechanism has not been elucidated yet. Thus, the present study aims to clarify the mechanisms of CBZinduced hepatorenal toxicity in rats. Therefore, we partitioned 40 male Wistar rats into four groups (n = 10): a negative control group and three treatment groups, which received 100, 300, and 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…In this study, HML-treated rats showed a decrement in their general activity, as well as, a significant drop in body weight was observed after exposure to HFM and HML regardless of having free access to food, indicating that both pesticides have a toxic effect on animal organs that may hinder the nutrient absorption [ 26 , 27 ]. Several studies confirmed our findings that insecticides caused weight loss, which could be attributed to the repellant effects of the insecticides causing a reduction in the consumption of food [ 28 , 29 ]. Behavioral assessment is an essential test for brain functions since changes in the nervous system affect human and animal behavior [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, HML-treated rats showed a decrement in their general activity, as well as, a significant drop in body weight was observed after exposure to HFM and HML regardless of having free access to food, indicating that both pesticides have a toxic effect on animal organs that may hinder the nutrient absorption [ 26 , 27 ]. Several studies confirmed our findings that insecticides caused weight loss, which could be attributed to the repellant effects of the insecticides causing a reduction in the consumption of food [ 28 , 29 ]. Behavioral assessment is an essential test for brain functions since changes in the nervous system affect human and animal behavior [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…Pesticides are extremely toxic to the kidneys, which are primarily responsible for excreting xenobiotics and related metabolites. [ 40 ] Serum urea and creatinine are biomarkers of the glomerular filtration rate, which is used in clinical research as an indicator of renal function. [ 25 ] The nephrotoxic potential of HML was revealed in our study by the elevation of serum urea and creatinine in rats exposed to either high or low doses of HML.…”
Section: Discussionmentioning
confidence: 99%
“…5 CBZ has toxic effects on humans, animals, and plants, 6 such as DNA damage, 7 reproduction and developmental defects, 8,9 and neuro-, 10 liver and kidney toxicity. 11 Therefore, the treatment of CBZ in water and soil is crucial. To cope with the environmental crisis and pollution problems, various methods have been developed to treat CBZ in water and soil, including adsorption, 12 thermal degradation, 13 biodegradation, 14 and photocatalytic degradation.…”
Section: Introductionmentioning
confidence: 99%